2023
DOI: 10.1093/mnras/stad889
|View full text |Cite
|
Sign up to set email alerts
|

The implications of large binding energies of massive stripped core collapse supernova progenitors on the explosion mechanism

Abstract: We examine the binding energies of massive stripped-envelope core collapse supernova (SECCSN) progenitors with the stellar evolution code mesa, and find that the jittering jets explosion mechanism is preferred for explosions where carbon-oxygen cores with masses of $\gtrsim 20 \, \mathrm{M}_\odot$ collapse to leave a neutron star (NS) remnant. We calculate the binding energy at core collapse under the assumption that the remnant is a NS. Namely, stellar gas above mass coordinate of ≃ 1.5 − 2.5 M⊙ is ejected in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Along the allowed region, the CSM mass is relatively well constrained to M CSM ≈ 2-4 M e . The SN ejecta is constrained to have an energy of 3 × 10 51 erg, which is slightly larger than typical values but still consistent with the stellar explosion scenario, potentially further enhanced by jets (e.g., Soker 2010;Papish & Soker 2011;Shishkin & Soker 2023).…”
Section: Application To Sn 2021qqpmentioning
confidence: 64%
“…Along the allowed region, the CSM mass is relatively well constrained to M CSM ≈ 2-4 M e . The SN ejecta is constrained to have an energy of 3 × 10 51 erg, which is slightly larger than typical values but still consistent with the stellar explosion scenario, potentially further enhanced by jets (e.g., Soker 2010;Papish & Soker 2011;Shishkin & Soker 2023).…”
Section: Application To Sn 2021qqpmentioning
confidence: 64%
“…The goal of this exploratory study is to estimate the expected contribution of jittering jets to gravitational wave emission from CCSNe. The motivation for this studyresults from recent studies that support the jittering jets explosion mechanism (JJEM) of CCSNe (e.g., Soker 2022aSoker , 2022cSoker , 2023bShishkin & Soker 2023), and the very recent study by Gottlieb et al (2023) who found that the turbulent cocoons that energetic relativistic jets form can be a strong source of gravitational waves. A cocoon is the convective bubble that a jet inflates, even if not relativistic (e.g., Izzo et al 2019), and is filled with the shocked jet's material and the shocked ambient material.…”
Section: Introductionmentioning
confidence: 99%